Pola Komunikasi Guru dan Orang Tua dalam Pembinaan Akhlak Peserta Didik - Puji Lestari (Institut Agama Islam Negeri Palopo, 2018)
This study uses a type of qualitative research (qualitative research), which aims.1), to determine the pattern of communication between parents and teachers in the moral development of students in SMA Negeri 2 Sukamaju District. Luwu Utara; 2) To find out the form of moral coaching of parents towards learning that is studying at SMA Negeri 2 Sukamaju district. Luwu Utara;3) to find out the form of moral coaching of students in schools conducted by the teacher; 4) to find out what is the teacher and teacher in the moral development of students. The results showed that 1) the pattern of communication and cooperation between parents and teachers in the moral coaching of students was good enough because there were parents and teachers in fostering the morality of students in SMA 2 Sukamaju; 2) There are several forms of parental moral coaching to students in SMA 2 Sukamaju; 3) Forms of Moral Coaching for Students in SMA 2 Sukamaju can be grouped into two forms of moral coaching, namely morality to humans, and the environment; 4) Constraints in the moral development of students are the family environment, association, and electronic media.